Contribution of neural circuits tested by transcranial magnetic stimulation in corticomotor control of low back muscle: a systematic review - Desmons, Mikaël; Theberge, Michael; Mercier, Catherine; Massé-Alarie, Hugo (Frontiers in Neuroscience, 2023)
Introduction: Transcranial magnetic stimulation (TMS) is widely used to investigate central nervous system mechanisms underlying motor control. Despite thousands of TMS studies on neurophysiological underpinnings of corticomotor control, a large majority of studies have focused on distal muscles, and little is known about axial muscles (e.g., low back muscles). Yet, differences between corticomotor control of low back and distal muscles (e.g., gross vs. fine motor control) suggest differences in the neural circuits involved. This systematic review of the literature aims at detailing the organisation and neural circuitry underlying corticomotor control of low back muscles tested with TMS in healthy humans. Methods: The literature search was performed in four databases (CINAHL, Embase, Medline (Ovid) and Web of science) up to May 2022. Included studies had to use TMS in combination with EMG recording of paraspinal muscles (between T12 and L5) in healthy participants. Weighted average was used to synthesise quantitative study results. Results: Forty-four articles met the selection criteria. TMS studies of low back muscles provided consistent evidence of contralateral and ipsilateral motor evoked potentials (with longer ipsilateral latencies) as well as of short intracortical inhibition/facilitation. However, few or no studies using other paired pulse protocols were found (e.g., long intracortical inhibition, interhemispheric inhibition). In addition, no study explored the interaction between different cortical areas using dual TMS coil protocol (e.g., between primary motor cortex and supplementary motor area). Discussion: Corticomotor control of low back muscles are distinct from hand muscles. Our main findings suggest: (i) bilateral projections from each single primary motor cortex, for which contralateral and ipsilateral tracts are probably of different nature (contra: monosynaptic; ipsi: oligo/polysynaptic); (ii) the presence of intracortical inhibitory and excitatory circuits in M1 influencing the excitability of the contralateral corticospinal cells projecting to low back muscles. Understanding of these mechanisms are important for improving the understanding of neuromuscular function of low back muscles and to improve the management of clinical populations (e.g., low back pain, stroke).